2018
DOI: 10.3389/fonc.2018.00146
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Race and Economic Characteristics in the Presentation and Survival of Patients With Surgically Resected Non-Small Cell Lung Cancer

Abstract: BackgroundLittle is understood regarding the inter-relation between economic, marital, and racial/ethnic differences in presentation and survival of surgically resected lung cancer patients. Our investigation will assess these differences in addition to known therapeutic, patient, and histopathologic factors.MethodsA retrospective review of the Surveillance Epidemiology and End Reporting database was conducted through the years 2007–2012. The population was split into nine different ethnic groups. Population d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
(17 reference statements)
1
16
0
Order By: Relevance
“…More interestingly, we discovered the marital status in uenced CSS of Uterine Sarcoma for the rst time. Evidences showed that unmarried patients exhibited shorter OS and CSS compared with married patients in lung and liver cancer [24,23]. In the present study, patients of Separated, Divorced and Widowed (SDW) had the worst survival compared to those married patients, followed by the single patients.…”
Section: Discussionmentioning
confidence: 44%
“…More interestingly, we discovered the marital status in uenced CSS of Uterine Sarcoma for the rst time. Evidences showed that unmarried patients exhibited shorter OS and CSS compared with married patients in lung and liver cancer [24,23]. In the present study, patients of Separated, Divorced and Widowed (SDW) had the worst survival compared to those married patients, followed by the single patients.…”
Section: Discussionmentioning
confidence: 44%
“…In this study,the routinely available characteristics of the patients were extracted from the database.Based on these,a nomogram was developed and validated.The model performance of the In agreement with other type of NSCLC,the age and sex were all important predictors for CSS of LCLC [13].Old age and male patients were associated with worse prognosis.In order to get better discrimination for the nomogram model,According to Harrell's guidelines,in this study,patients age were determined into two groups [14].Seventy-seven years old was the best cutoff point.At present,an consistent conclusion was not reached for the CSS disparities of patients with lung cancer for different race [15].In genaral,better CSS outcomes would be seen in race with higher health awareness,that the treatment in these races would be more active.In this study,as for LCLC,the significantly different influence of race for patient's CSS was seen both in univariable and multi-variable analysis.The CSS outcome for other race is better than the White race.Treatment activity might be a possible explanation for this phenomenon,another reason might be attributed to the sample of the SEER database,that small proportion of other race was collected in the database,which might affect the statistical results for this study.As a most common used tumor associated indices,the AJCC stage still contributed most for the established nomogram model,which is in line with other type of NSCLC [16].Tumour size is an important indicator for T stage,in this study,its was also found to be an independent risk factor for LCLC.It could be confirmed that patients with a tumour size >41mm show less CSS time than that <=41mm with the maximally selected rank statistics.Surgery is the domain treatment for many type of lung cancer.In this study,surgery was also found to be an important treatment for LCLC that patients with surgery had a greatly decrease in cancer-specific death.Marital status has been confirmed to be associated with the CSS in a series of cancer [17][18][19][20][21].This phenomenon, in our present study was consistent with the previous study that married LCLC patients represented for lower nomogram scores had CSS benefit compared with other types of marital status.…”
Section: Discussionmentioning
confidence: 65%
“…Evidences showed that unmarried patients exhibited shorter OS and CSS compared with married patients in lung and liver cancer [24,23]. In the present study, patients of Separated, Divorced and Widowed (SDW)…”
Section: Discussionmentioning
confidence: 70%